2021
DOI: 10.1177/03611981211031884
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Lateral Dimension of Traffic: Measuring and Modeling Lane Discipline

Abstract: There is growing interest in understanding the lateral dimension of traffic. This trend has been motivated by the detection of phenomena unexplained by traditional models and the emergence of new technologies. Previous attempts to address this dimension have focused on lane-changing and non-lane-based traffic. The literature on vehicles keeping their lanes has generally been limited to simple statistics on vehicle position while models assume vehicles stay perfectly centered. Previously the author developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, it was found that longitudinal velocity affects not only average lateral velocity and acceleration but also their dispersion. In specific terms, their dispersion parameter depends linearly on longitudinal velocity, a result that is consistent with earlier findings ( 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, it was found that longitudinal velocity affects not only average lateral velocity and acceleration but also their dispersion. In specific terms, their dispersion parameter depends linearly on longitudinal velocity, a result that is consistent with earlier findings ( 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…A possible explanation for this behavior is the better perspective and, therefore, the greater control drivers have with regard to what occurs on their left because of being seated on that side of their vehicle (in countries such as Germany where traffic drives on the right-hand side of the road). The same reasoning would also explain why the average lateral position of the vehicles is to the left of the center of the lane ( 2 , 18 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, lateral movement has not been sufficiently investigated in simulation-based studies. Recently, Delpiano [31] recommended a study of the lateral dimension according to CAV behaviour. Aimsun developers demonstrated the feasibility of calibrating these parameters in their traffic model.…”
Section: Literature Reviewmentioning
confidence: 99%